Transformation of Religious Tourism Destinations from Pilgrimage to Mosques: A Case Study of the Sheikh Zayed Mosque in Solo, Indonesia - Adinugraha , Hendri Hermawan; Shulthoni, Muhammad (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
Visiting religious tourism destinations to mosques is currently becoming a trend among Indonesians. Social changes in society in choosing religious tourism destinations are relevant topics for research. This study intends to explain the phenomenon of the transformation of religious tourism visit destinations from pilgrimages to the Sheikh Zayed Mosque in Solo. This study used a qualitative research method that uses data collection techniques through observation, interviews, and documentation. The data sources in this study are the community around the Sheikh Zayed Mosque, visitors, and managers of the Sheikh Zayed Mosque. The data were analyzed using data reduction techniques, data presentation, and conclusions. The empirical findings of this study have shown that there has been a shift in the goals of religious tourism destinations from those that used to be pilgrimages to tombs and have now shifted to visits to major mosques, one of which is the Sheikh Zayed Mosque. Based on the results and findings of this study, it can be concluded that transformation is closely related to the changes from one form to another. The findings of this study explain the process of transforming a religious tourism destination, which is usually a pilgrimage to a visit to the Sheikh Zayed Mosque. The existence of the Sheikh Zayed Mosque has been proven to have a better financial impact on the surrounding community.